2018
DOI: 10.3928/23258160-20180221-07
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal Vascularity Index in Retinitis Pigmentosa: An OCT Study

Abstract: Patients with RP showed a significant reduction in CVI and an increase in CT as compared to normal eyes. [Ophthalmic Surg Lasers Imaging Retina. 2018;49:191-197.].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 24 publications
1
29
0
Order By: Relevance
“…Tan and associates evaluated the structural changes in the choroid of patients with RP and showed a significant reduction in CVI as compared to normal eyes [23]. A lower CVI in RP supports the concept that choroidal vascular defects can influence the manifestation and progression of the disease.…”
Section: In Inherited Retinal Disordersmentioning
confidence: 80%
See 1 more Smart Citation
“…Tan and associates evaluated the structural changes in the choroid of patients with RP and showed a significant reduction in CVI as compared to normal eyes [23]. A lower CVI in RP supports the concept that choroidal vascular defects can influence the manifestation and progression of the disease.…”
Section: In Inherited Retinal Disordersmentioning
confidence: 80%
“…A lower CVI in RP supports the concept that choroidal vascular defects can influence the manifestation and progression of the disease. Therefore, CVI could be used as surrogate marker in monitoring and analyzing the progression of RP [23].…”
Section: In Inherited Retinal Disordersmentioning
confidence: 99%
“…16 The utility of CVI to evaluate choroidal vasculature was also validated in common ocular and systemic diseases. 15,[32][33][34][35][36][37][38] In this study, cigarette smoking was shown to be associated with decreased CVI and not CT. This effect may arise from decreased LA or increased SA or a combination of both in chronic smokers.…”
Section: Discussionmentioning
confidence: 91%
“…Agrawal et al 15 found that CVI increased in both acute CSC eyes and fellow eyes. Tan et al 26 reported that patients with retinitis pigmentosa showed reduced CVI when compared with normal eyes. Thus CVI has evolved into a noninvasive tool for studying structural changes in the choroid and monitoring retinal and choroidal diseases.…”
Section: Discussionmentioning
confidence: 99%